Evaluating Circadian Dysfunction in Mouse Models of Alzheimer’s Disease: Where Do We Stand? - Sheehan, Patrick W.; Musiek, Erik S. (Frontiers in Neuroscience, 2020)
Circadian dysfunction has been described in patients with symptomatic Alzheimer’s Disease (AD), as well as in presymptomatic phases of the disease. Modeling this circadian dysfunction in mouse models would provide an optimal platform for understanding mechanisms and developing therapies. While numerous studies have examined behavioral circadian function, and in some cases clock gene oscillation, in mouse models of AD, the results are variable and inconsistent across models, ages, and conditions. Ultimately, circadian changes observed in APP/PS1 models are inconsistent across studies and do not always replicate circadian phenotypes observed in human AD. Other models, including the 3xTG mouse, tau transgenic lines, and the accelerated aging SAMP8 line, show circadian phenotypes more consistent with human AD, though the literature is either inconsistent or minimal. We summarize this data, and provide some recommendations to improve and standardize future studies of circadian function in AD mouse models.